Performance of flexible membrane using kaolin dynamic membrane in treating domestic wastewater - Megat Mohd Noor, Megat Johari; Ahmadun, Fakhrul Razi; Mohamed, Thamer Ahmad; Muyibi, Suleyman Aremu; Pescod, M.B. (Elsevier, 2002)
A study using a laboratory experimental rig with a tubular configuration microfiltration fabric membrane in treating secondary effluent from domestic waster treatment plant was carried out. Several inert materials; kaolin (both heavy and light), diatomite and Fuller's earth, were studied to identify an appropriate dynamic membrane material. Heavy kaolin was found to be effective and relatively easily to clean. A rapid decline in flux was observed when filtering the secondary effluent with a turbidity of about 5 NTU without using a dynamic membrane. The development of a heavy kaolin dynamic membrane was found to be a function of the kaolin concentration and crossflow velocity. However varying crossflow velocities within a limited range, such as 1.6 and 2.5 m/s produced a similar steady state flux. Permeate turbidity, which is an indication of the formation status of a dynamic membrane, improved with higher kaolin concentration and reduced with increasing crossflow velocity, within the range considered. The time taken to produce low permeate turbidity (of less than 1 NTU) was shorter with a higher heavy kaolin concentration. A similar steady state permeate turbidity is reached after prolonged filter run despite using a low heavy kaolin concentration. It was also found that a 10-min membraning time at heavy kaolin concentration of 333 mg/l was enough to lay the dynamic membrane before proceeding with filtering the secondary effluent. Permeate turbidity as low as 0.2 NTU could be attained. Secondary effluent was found unsuitable to be applied as a membraning liquid. The purity of membraning or carrier liquid was crucial in the production of an effective dynamic membrane. Feed concentrates turbidity was noticed to increase with the semi-continuous feeding. However, it does not have a significant impact on the permeate turbidity unlike when introducing a new batch of feed regardless of its concentration level.